2019
DOI: 10.1080/14786419.2019.1582037
|View full text |Cite
|
Sign up to set email alerts
|

A new triterpenoid and a new flavonoid glycoside isolated from Bupleurum marginatum and their anti-inflammatory activity

Abstract: This study to investigate chemical constituents from the aerial of Bupleurum marginatum led to the isolation of a new trierpenoid and a new flavonoid, namely 3β-hydroxy-cycloart-24-en-26-acetyloxy (1), and 3, 3', 5'-trimethoxyl-myricetin 7-O-β-D-glucopyranoside (2) along with eight known compounds (3-10). Their structures were established by spectral data analyses (MS, 1D and 2D NMR), as well as by comparison of spectral data with those of the related known compounds. The 24-en-lanostane type triterpenoid with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…A diverse range of biological activities have also been reported for spirocyclopropanes, such as anti-inflammatory, analgesic, anticancer, and cytotoxic activity [ 19 , 20 , 21 , 22 ]. The attention from compounds that incorporate this structure has not been limited to molecules of synthetic origin, but rather have focused on natural products because this functionality has been reported in several naturally occurring compounds [ 23 , 24 , 25 , 26 ]. In the case of spirocyclopropanes bound to heterocycles there are few reports of biological activity.…”
Section: Introductionmentioning
confidence: 99%
“…A diverse range of biological activities have also been reported for spirocyclopropanes, such as anti-inflammatory, analgesic, anticancer, and cytotoxic activity [ 19 , 20 , 21 , 22 ]. The attention from compounds that incorporate this structure has not been limited to molecules of synthetic origin, but rather have focused on natural products because this functionality has been reported in several naturally occurring compounds [ 23 , 24 , 25 , 26 ]. In the case of spirocyclopropanes bound to heterocycles there are few reports of biological activity.…”
Section: Introductionmentioning
confidence: 99%
“…Although the structure–activity relationships of cycloartane triterpenes have not been thoroughly investigated, it was suggested that the exo ‐methylene‐γ‐lactone ring system plays an important role in the inhibitory effects on TNF‐α‐induced NF‐κB activity and NO‐production (Youn et al, 2016). 3β‐Hydroxy‐26‐acetyloxy‐cycloart‐24‐ene ( 37 ) was isolated from Bupleurum marginatum and was evaluated by its antiinflammatory effects (Lei et al, 2020), being able to inhibit the NF‐κB induction by 60.61%.…”
Section: Antiinflammatory Activity Of Natural Triterpenesmentioning
confidence: 99%
“…With 8 NP classes, the total number of test cases is then 40. The refs report new NP elucidation of families that we are interested in (see Tables S10–S17). Six different XGBoost models were tested on these cases: five models with the hyperparameters that achieved the highest f1-scores while training with the different resampling techniques and a model that employed a different input representation.…”
Section: Test Casesmentioning
confidence: 99%